The darkest sides of politics. - Bale, Jeffrey M., author.
1 online resource
Keywords: This book examines a wide array of phenomena that arguably constitute the most noxious, extreme, terrifying, murderous, secretive, authoritarian, and/or anti-democratic aspects of national and international politics. Scholars should not ignore these "dark sides" of politics, however unpleasant they may be, since they influence the world in a multitude of harmful ways. The second volume in this two-volume collection focuses primarily on assorted religious extremists, including apocalyptic millenarian cults, Islamists, and jihadist terrorist networks, as well as CBRN (chemical, biological, radiological, and nuclear) terrorism and the supposedly new "nexus" between organized criminal and extremist groups employing terrorist operational techniques. A range of global case studies are included, most of which focus on the lesser known activities of certain religious extremist milieus. This collection should prove to be essential reading for students and researchers interested in understanding seemingly arcane but nonetheless important dimensions of recent historical and contemporary politics.